Brown Garden Snail, Helix aspersa Müller (Gastropoda: Pulmonata: Helicidae) - Geo W. Dekle; Thomas R. Fasulo (EDIS)
The brown garden snail (European brown snail) Helix (Cyptoomphalus) aspersa Müller, was described by O.F. Müller in 1774 from specimens collected in Italy. This plant feeder has been disseminated into many parts of the world intentionally as a food delicacy, accidentally by the movement of plants, and by hobbyists who collect snails. It was introduced to California in the 1850s as a source of escargot. It has adapted well to California and is very troublesome as a pest of crops and ornamentals (Capinera 2001). This document is EENY-240 (originally published as DPI Entomology Circular 83), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: October 2001. Revised: August 2002.